Significance of protection of the meadow and grassland communities for maintenance the floristic diversity in the area of the south-eastern Silesian Upland (Poland) - Babczyńska-Sendek, Beata (Biodiversity: Research and Conservation, 2010)
Variety of relief and geology of the south-eastern Silesian Upland results in richness and diversity of its vegetation. Wet meadows and xerothermic grasslands are one of its most valuable components. In their phytocoenoses many protected (27 in meadows and 22 in grasslands) and rare (25 and 34) species have been noted. Among them there are threatened species put on the "Red list of the vascular plants in Poland". A few species represent the mountain element. Some meadow and grassland phytocoenoses from the south-eastern part of the Silesian Upland are characterised by exceptionally high floristic richness. The Cirsietum rivularis patches have proved to be the richest among them. Large-scale cessation of usage caused that meadows and grasslands actually need urgent active protection here. This is the only chance of survival for many rare protected and threatened plants.